Response of optimum nitrogen rate in maize with legume intercropping system (SAARC Journal of Agriculture, 2017)
A field experiment was conducted at S.V. Agricultural College farm (ANGRAU), Tirupati, India during rabi, 2009-10. The experiment was consisted of five system treatments (sole maize at 60 x 20 cm sowing, sole maize in skipped row sowing, maize in skipped row + greengram, maize in skipped row + blackgram and maize in skipped row + cluster bean) and three nitrogen doses (100, 75 and 50% recommended dose of nitrogen). The treatment combinations were laid out in factorial randomized block design with three replications. Yield attributes and grain yield of maize were maximum with sole maize at 60x20cm spacing but at par with maize + cluster bean, maize + blackgram and maize + greengram intercropping system. The lowest parameters were observed with sole maize sown in skipped rows. All the parameters were maximum with the application of 100% recommended dose of nitrogen to maize, but comparable with that of 75%. The maize equivalent yield, land equivalent ratio and benefit cost ratio were higher with maize + cluster bean intercropping as compared to other treatments. The result revealed that among the different maize intercropping systems tested, maize in skipped rows + cluster bean with 75% recommended dose of nitrogen to maize was found economically profitable.SAARC J. Agri., 15(1): 139-148 (2017)